2016
DOI: 10.3109/13880209.2015.1087035
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of pomegranate peel against hematotoxicity, chromosomal aberrations, and genotoxicity induced by barium chloride in adult rats

Abstract: Context Pomegranate peel (PP) has health benefits including antibacterial, antioxidant, antiinflammatory, and antimutagenic properties. Objective This study investigated the biochemical composition and protective effects of PP against hematotoxicity and genotoxicity induced by barium chloride (BaCl 2 ) in adult rats. Materials and methods Adult Wistar rats were divided into four groups of six each: control, barium (67 ppm via drinking water), PP (5% via diet), and their combination during 21 d. Oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Our results were in accordance with those of Tarskikh (34) who has reported that acute acrylamide toxicity can damage erythrocyte membrane and decrease its hemolytic resistance. The alteration in erythrocyte parameters and intravascular hemolysis of barium treated rats are considered as a consequence of oxidative stress and lipid peroxidation in the circulating erythrocytes (35). Our data showed a significant increase of MDA concentrations as a result of oxidative stress and an excess production of ROS probably generated by ACR.…”
Section: Analytical Parameters Mean Valuesmentioning
confidence: 50%
“…Our results were in accordance with those of Tarskikh (34) who has reported that acute acrylamide toxicity can damage erythrocyte membrane and decrease its hemolytic resistance. The alteration in erythrocyte parameters and intravascular hemolysis of barium treated rats are considered as a consequence of oxidative stress and lipid peroxidation in the circulating erythrocytes (35). Our data showed a significant increase of MDA concentrations as a result of oxidative stress and an excess production of ROS probably generated by ACR.…”
Section: Analytical Parameters Mean Valuesmentioning
confidence: 50%
“…for 30 days; Kumar et al, 2013) and paraquat (Mowery et al, 2018). Likewise, it protected against barium chloride-induced oxidative stress and subsequently its hematotoxic, genotoxic (Elwej, Ben Salah, et al, 2016;Elwej, Grojja, et al, 2016), and nephrotoxic actions . Additionally, a pilot study indicated that pomegranate polyphenols (POMx, which is ellagitannin-enriched pomegranate polyphenol extract prepared from juice biowaste pressing; Rasheed et al, 2009) daily supplementation (753 mg polyphenols)…”
Section: Antioxidant Activitymentioning
confidence: 96%
“…Several studies pointed to the hepatoprotective effect of PP using different hepatotoxicity and liver fibrosis-induced models (Doostan et al, 2019;Elwej, Ben Salah, et al, 2016;Elwej, Grojja, et al, 2016;Hafiz et al, 2016;Mukherjee et al, 2013;Shaban et al, 2013;Wei et al, 2015), and further autoimmune hepatitis (Wang, Özen, et al, 2018;Wang, Men, et al, 2018). It improved the liver function tests as manifested by a decrease in aspartate aminotransferase (AST), alanine aminotransferase (ALT; Doostan et al, 2019;Elwej, Ben Salah, et al, 2016;Elwej, Grojja, et al, 2016;Shaban et al, 2013;Wei et al, 2015), γ-glutamyl transpeptidase (GGT; Elwej, Ben Salah, et al, 2016;Elwej, Grojja, et al, 2016), total bilirubin and increased albumin levels.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that pomegranate peel could possess in vitro thrombolytic activity when added to clots formed from human blood samples, extracts of it were reported to cause prolonged bleeding and thrombin time [12]. In addition to its reported ability to alter Prothrombin time (PT), reduce platelet aggregation and protect against hematotoxicty [1316].…”
Section: Introductionmentioning
confidence: 99%